Audio-Visual as Media in Reading: Students’ Responses and Challenges - Neng Eva Loviasyuni; Gartika Pandu Bhuana (Institut Agama Islam Negeri Palopo, 2023)
Some experts believe that audio-visual media is beneficial in learning a second language, including English. It can increase not only students’ motivation to learn, but also their focus on the learned material. In reading, audio-visual media is considered effective in enhancing students’ comprehension. Most of the studies focus on the positive impact of using audio-visual media, but they have not yet investigated the obstacle that might be experienced by the students on its usage. Therefore, this study intends to examine the students’ obstacles of using audio-visual media in reading as well as their responses to its implementation. The qualitative method was applied. The data were gained through questionnaires and observation. The respondents were 37 ninth-grade students. The findings revealed that although the students responded positively to the use of audio-visual media in reading, they had issues with its implementation. The issues dealt with language and comprehension. In the term of language, the students found it hard to understand the meaning of some words. As a result, it impacted their comprehension. Thus, it is suggested for the teachers to first consider the students’ vocabulary mastery before using audio-visual media in teaching reading. If the students have a limited vocabulary, they can use a video that has familiar words known by the students.